Optimizing the use of nirmatrelvir/ritonavir in solid organ transplant recipients with COVID-19: A review of immunosuppressant adjustment strategies - Tang, Yangming; Li, Yue; Song, Turun (Frontiers in Immunology, 2023)
The COVID-19 pandemic has caused significant burden of morbidity and mortality worldwide, with solid organ transplant recipients (SOTRs) being particularly vulnerable. Nirmatrelvir and ritonavir have demonstrated potential in reducing the risk of hospitalization and death in patients with mild-to-moderate COVID-19. However, ritonavir has a strong drug-drug interaction with CYP3A-dependent drugs such as calcineurin inhibitors, potentially leading to rapid increases in blood concentration. As SOTRs are commonly prescribed immunosuppressants, co-administration with nirmatrelvir/ritonavir requires careful consideration. To address this issue, we conducted a literature review to evaluate the use and adverse effects of nirmatrelvir/ritonavir in SOTRs and explore feasible immunosuppressant adjustment regimens. Our findings suggest that nirmatrelvir/ritonavir could be a feasible treatment option for COVID-19 in SOTRs, provided that appropriate immunosuppressive drug management is in place during co-administration. Although prescribing the novel anti-SARS-CoV-2 drug to transplant recipients poses challenges, potential strategies to overcome these issues are discussed. Further studies are needed to determine the optimal dosing strategies of nirmatrelvir/ritonavir, immunosuppressants adjustment and monitoring in this patient population.